'Our voice started off as a whisper and now it is a great big roar': The Salford Dementia Associate Panel as a model of involvement in research activities. (January 2020) - Bowker, Ron; Calvert, Lesley; Allcroft, Frances; Bowker, Gail; Foy, Pat; Gandy, Jackie; Jones, Sandra; Bushell, Sophie; Clark, Andrew; Innes, Anthea
This paper presents the work of the 'Salford Dementia Associate Panel', based at the Salford Institute for Dementia, Salford University (UK). We discuss the roles of the Dementia Associates, in particular around the areas of engagement and research. The panel is made up of people living with dementia, and current and former care partners. It highlights the development of this group over a four-year period and demonstrates over time how the role of a Dementia Associate member has evolved. The panel is involved in research, education and public engagement activities conducted by staff and students within the Institute. The motivations for becoming involved are clearly articulated and demonstrate how the personal backgrounds of individuals have driven the collective involvement and desire to bring about change. The benefits and challenges associated with working as part of a panel are discussed. We conclude by bringing together our experiences as a set of suggestions for others who may wish to create a similar forum to promote the involvement of people living with dementia and former and current care partners.